Analisis Perkawinan Paksa Sebagai Tindak Pidana Kekerasan Seksual Dalam Rancangan Undang-Undang Penghapusan Kekerasan Seksual PKS - M Mohsi (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2020)
Marriage guardian is the most important element in marriage, its existence determines the validity of a marriage. In classical fiqh, the type of marriage guardian has been constructed to be the guardian of mujbir and the guardian of ghairu mujbir. Axiologically, wali mujbir is positioned as a person who can marry his daughter with a very high legality, of course with certain conditions, not merely coercion (ikrah). However, in its implementation, the position of the guardian mujbir is very strong without any limitation of motion, may even force the will in the matter of marrying his child, even though the child does not approve of it. The PKS Bill, which was once a subject of discussion, included the imposition of marriage in the article on sexual violence and bring up a disagreement in the socoiety. This article was a qualitatif research which is using two aproach that are conseptual approach and statute approach. The result show through the observer's observations, it was in an effort to straighten out a distorted understanding of the guardianship rights of the guardian mujbir that had been patented by some social constructs in Indonesia.